REPORTING THE LOCATION OF WASTE COLLECTION IN ANDROID BASES SYSTEM IN BANDA ACEH CITY - Sarini Vita Dewi; Riky Yahdin (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2020)
Trash is a common problem in almost every city in Indonesia, including in Banda Aceh, although not as much as in other cities in the country. The trash's pile is increasing day by day resulting delays in handling by the management. Over time the piles of trash will accumulate and cause another problems, such as strong odors, disease spread, traffic disruption, and flooding. To overcome it, cooperation between the Sanitation Service and the community is needed, therefore an application is made that can be a way for sharing information about the location of trash piles for sanitation officers and related parties. So that later each user can find out exactly where the trash pile is located. This application system is built on a mobile basis for the client side, users use an Android-based on Smartphone or Tablet Computer. This application connects users to the server side by sending location data of coordinate points to be responded by the server by mapping the user's location on the Google Map with the Google Map API.